Factors Influence the Growth of Women Owned Microfinance Institutions in Wolaita Zone, Southern Ethiopia (International Journal of Food and Nutritional Sciences, 2022)
Objective: The aim of this study was to explain the factors influencing the growth of women owned microfinance institutions in Wolaita Zone, Southern Ethiopia. Theoretical frame work: The financial, institutional and demographic factors are important tool that affects the growth of microfinance institutions.Methods: The researchers used a simple random sampling method to select 399 respondents from the purposively selected districts of Wolaita Zone. The finding was analyzed using the software Packages such as SPSS and smart PLS-SEM. Descriptive and inferential statistics was used to analyze the data.